Late pregnancy analysis with Yunban’s remote fetal monitoring system - Qiuping Wang; Weihua Yang; Lie Li; Guokai Yan; Huihui Wang; Jianqiang Li (International Journal of Distributed Sensor Networks)
With the adoption of the two-child policy, there has been a large increase in women of older maternal and high-risk pregnant women. So, it is necessary to analyze the health status of women in the late pregnancy on time. To analyze the effect on using remote fetal monitoring on women in the late pregnancy, we selected women in the late stage of pregnancy in our hospital as research subjects. They were randomly divided into two groups: the experimental group, which engaged in remote fetal monitoring, and the control group, which adopted traditional cardiac monitoring. In order to get more effective data, we used the Kalman filter and audio repair algorithms to preprocess the collected data. During follow-up observation, we compared the two groups using neonatal cardiac monitoring by employing the non-stress test and observed the occurrence of neonatal asphyxia. The incidence of neonatal abnormal non-stress test in the experimental group and the control group was 33.6% and 17.3%, respectively; the difference was statistically significant ( p  < 0.05). The incidence of neonatal asphyxia in the experimental group was 12.5%, which was significantly lower than in the control group (30%; p  < 0.05). We have found that women in the late stage of pregnancy who adopted remote fetal monitoring could detect abnormal non-stress test earlier and thus increase in the detection of rate of neonatal asphyxia.